A Criticism on the Book "Folklore Culture" - Fereshteh Aliani; Moharram Rezayati (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Academic textbooks should be written in a way that meets the needs of the audience in various related scientific and research fields. To this end, critical evaluation of academic texts is a vital step in the consistency of any discipline and its curriculum. This need is especially felt in the recently established field of Folklore literature. The books that have been written so far about the basics of this newly established discipline are not more than a limited number, but these studies are expanding day by day, so it is vital to criticize these sources in order to improve the quality of the books. Undoubtedly, every written text has useful and significant aspects, and it probably has some issues that reminding and solving would result in the work`s edition. With this description, in order to achieve such a goal, the present article, with a descriptive-analytical method and a critical approach, reviewed one of the most important books in the field of Folk literature, namely "Folklore Culture". The most important results of this research are shortcomings such as not addressing the research background of the issues raised, generalization in some cases, purely descriptive approach, lack of organized connection between theory and other parts of the book, etc., as well as finding the advantages and innovative aspects of this book. This work, with minor modifications, can be valuable work for researchers in the field of Folk literature.